Angiogenesis and Metastasis Inhibitors for the Treatment of Malignant Melanoma - Riichiro Abe; Yasuyuki Fujita; Sho-ichi Yamagishi (Mini Reviews in Medicinal Chemistry, 2007)
Malignant melanoma is one of the most highly invasive and metastatic tumors. Melanoma is an increasingly common malignancy as well, and its mortality rates have been rapidly increasing above those of any other cancer in recent years. Surgical resection and systemic chemotherapy are the main therapeutic strategies for the treatment of malignant melanoma. However, these approaches are insufficiently effective and may be associated with significant adverse effects. Angiogenesis, a process by which new vascular networks are formed from pre-existing capillaries, is required for tumors to grow, invade and metastasize. Tumor vessels are genetically stable, and less likely to accumulate mutations that allow them to develop drug resistance in a rapid manner. Therefore, targeting vasculatures that support tumor growth, rather than cancer cells, is considered the most promising approach to malignant melanoma therapy. Now, novel anti-angiogenic agents with tolerable side effects is actually desired for the treatment of patients with malignant melanoma. In this paper, we review the current understanding of anti-angiogenic therapy for malignant melanoma, especially focusing on pigment epithelium-derived factor (PEDF), which was recently identified as the most potent endogenous inhibitor of angiogenesis in the mammalian eye. We also discuss here the involvement of a receptor for advanced glycation end products (RAGE) in angiogenesis, melanoma growth and metastasis, and the therapeutic implications of the blockers of RAGE in this devastating disorder.
Keywords: basic fibroblast growth factor